STRATEGI ADAPTSI SANTRI PONDOK PESANTREN TEKNOLOGI RIAU - Mardiah, Putri; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Schools. This research was conducted at the Riau Technology Islamic Boarding School, whose research object was students at the MTs level who had never previously been students, namely the new students of the Riau Technology Islamic Boarding School, teaching 2019/2020. This study aims to determine the adaptation strategy of the students of the Riau Technology Islamic Boarding School. This research uses qualitative research methods, namely by conducting data collection, conducting interviews, managing and analyzing them by looking for and finding patterns, finding what can be learned and what is important, and deciding what to tell others later, also by way of calling. research documentation. In this study there were 5 (five) subjects, namely subjects of transitional age from children to adolescents. The results of this study state that these students adapt by getting used to the existing regulations in the Riau Technology Islamic Boarding School environment, the students also learn to adapt in managing both time and completing all the needs that exist in the pesantren environment, students can also adapt well to fellow students so that the students can create good togetherness with one another. Key Words: Adaptation, Student Islamic Boarding School